Analisis Masalah Terkait Obat di Lima Rumah Sakit Tahun 2010 - MAX JOSEPH HERMAN; IDA DIANA SARI (Fakultas Farmasi Universitas Pancasila, 2012)
Drug prescribing and drug use become more complex, as the number and potency of available drugs increase, leading to a variety of Drug Related Problems (DRPs). From 15 studies conducted in several countries, 7.1% of the overall hospital admissions were related to DRPs and 59% of them might be prevented. For the last few decades, attention to DRPs in some countries like USA, Australia and England have increased. A study on pediatric inpatients was carried out in 2007 by monitoring medical records detected nearly 60% DRPs with an average of 3 DRPs per patient and other study done showed that more than 78% of geriatric patients had in average 3 DRPs. A retrospective study to identify morbidities related to DRPs has been conducted in 2010 in 5 hospitals having clinical pharmacy unit. Data were collected from medical records or clinical pharmacy documents and interviews with the head of pharmacy unit and clinical pharmacist. DRPs data were then analyzed and categorized according to a combination of American Society of Hospital Pharmacists (ASHP) and Pharmaceutical Care Network of Europe (PCNE) classifications. Results of the study revealed that there were 266 DRPs identified with an average of two DRPs per patient and anti-infection drugs were mostly involved. Duration of a treatment longer than necessary was found in 17.3% cases and had resulted in high cost drug treatment (32.7%), whilst poly-pharmacy, inappropriate drug form and new indication for drug treatment presented were hardly found. Pharmacist was the most likely who made intervention in DRPs (61.3%) and 48,9% intervention was proposed, but was rejected by prescriber.